Practising change together – where nothing is clear, and everything keeps changing. (2nd January 2020) - Sharp, Cathy
ABSTRACT: This paper explores the thinking and practice of 'action inquiry' an embedded learning practice that can help navigate complexity when practising change together. The paper uses examples from social contexts where there are concerns about community wellbeing and health care. These are drawn from collaborative or collective leadership development programmes within public services that seek to bring new attention to the qualities of how people think, converse and interact, as part of their collective professional practice. This treats social action as a relational and dialogical practice, something that we do together as professionals by engaging in reflective inquiry and action. The paper suggests that action inquiry offers a prospect of rekindling the links between 'action learning' and collaborative leadership by developing a co-mission and a mutual commitment to a new type of learning partnership. Action inquiry can be wrapped around and enmeshed within initiatives and programmes that work with complexity, anywhere where effective social action will depend on the quality of relationships that can be developed. This research was funded by two separate Scottish Government commissions, where the author was a learning partner. The paper also draws on the further reflections of some of the practitioners most centrally involved.